Pancasila sebagai Perekat Kebhinekaan Bangsa - Hamdy Sukra Laden; Novi Permita Sari (International Forum of Researchers and Lecturers, 2025)
Pancasila serves as the cornerstone of the Indonesian state and way of life, and it is crucial in fostering diversity. Maintaining unity is difficult for Indonesia because of its ethnic, cultural, religious, and linguistic diversity. These disparities can be brought together by the moral and ethical pillars of Pancasila, which include Divinity, Humanity, Unity, Democracy, and Justice. This article explores how Pancasila can serve as a framework for resolving possible disputes and fostering intergroup tolerance. It is desired that variety would continue to be the primary strength of the Indonesian people by emphasizing the application of Pancasila values in daily life. This study uses a qualitative approach with a descriptive analysis method to explore the strategic role of Pancasila in the context of diversity. The results of the study show that strengthening the understanding and practice of Pancasila values ​​in all levels of society is the key to success in maintaining unity amidst the nation's diversity.